THE INFLUENCE OF THE NUMBER OF RIPPLE OF POLYACRYLONITRILIC FIBERS COTTON TYPE ON YARN PROPERTIES - HRISTIAN Liliana; BORDEIANU Demetra Lacramioara; BŐHM-RÉVÉSZ Gabriella (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2016)
In this study we aimed the influence of the number of undulations of polyacrylonitrile fibers, cotton type, on the properties of yarns with Nm50/1 fineness, made on BD 200 the rotor spinning machine. Rotor spinning of the synthetic fibers is largely influenced by some characteristics of the fibers as being: the quality and quantity of the avivage, frequency of undulations and the number of defects fiber. Tensile properties and structural characteristics aspect of the yarns carried on BD 200 rotor spinning machine are determined, at the fiber content, the structural model and the technological parameters of processing, by the result of the transfer of fibers proprieties, into the meaning fiber-yarn. The yarns structural compactness, determined by the degree of twisting and tensional properties are defining for the quality of yarns and warrants the corresponding to their destination. Structural characteristics of the yarns which are characterized by complexity and diversity of their actions were studied by determining the linear irregularity (U%) , standard deviation (CV%) and the imperfections in the form of thinning (S), thickening (G), neppines (N), relative to 1000 m yarn.